Urgensi Sikap Profesional Dalam Meningkatkan Kepercayaan Konseli terhadap Konselor - Kusmiati, Meti; Rohmatullah, Niam (Ikatan Dai Indonesia, 2022)
As a service worker, a counselor is required to be a professional. Where a professional is someone who is an expert in their field, easy to adapt to their environment, easy to manage their time and attitude. Becoming a professional counselor is regulated in a counseling code of ethics that must be maintained and carries counseling principles that can facilitate counseling services. The performance of a counselor is spread across various fields, because basically every field requires guidance and the counselor is an expert in terms of guidance and development. The professionalism of a counselor is not only in terms of work, there are several criteria for a counselor to be considered a professional. This professionalism can create a positive influence for counselors and counselees. The counselee will put his trust in a professional counselor.